Traditional neonatal care practices in Jordan: A qualitative study. (27th June 2018) - Mrayan, Lina; Abujilban, Sanaa; Abuidhail, Jamila; Alshraifeen, Ali
Abstract: Traditional practices during the first months of neonatal life are common in developing countries, such as Jordan. Many international studies and reports have highlighted the fact that traditional neonatal practices are the cause of high neonatal mortality and morbidity rates in some countries. The aim of the present study was to identify neonatal care practices in Jordan. A descriptive, qualitative research design was used across four Jordanian cities across diverse regions. Forty mothers of neonates were interviewed over a period of 6 months (from January to June 2016). Thematic and content analysis was undertaken following Braun and Clarke's six step analysis. The results indicated that in Jordan, home‐based neonatal care comprises non‐biomedical practices. Rubbing the neonate's skin with salt, swaddling, prelacteal feeding, and other treatment modalities are common. Further studies are necessary to determine and report on the pros and cons of these practices in regard to neonatal health.